Feasibility Study of Plastic Waste Pyrolysis from Municipal Solid Waste Landfill with Spent FCC Catalyst: 10.32526/ennrj/21/202200270 - Chotiratanasak, Jiraphan; Vitidsant, Tharapong; Khemkhao, Maneerat (Environment and Natural Resources Journal, 2023)
Globally, there is growing concern about the problem of plastic waste. The majority of plastic waste is dumped into landfills, where it occupies space, reducing landfill capacity and causing a variety of environmental issues. Plastic waste pyrolysis has gained popularity because it can reduce the volume of plastic waste while also producing alternative fuels. This study assessed the feasibility of producing fuel oil from plastic waste using the catalytic pyrolysis process. Polyethylene (PE), polypropylene (PP), and polystyrene (PS) waste samples were collected from municipal solid waste (MSW) landfills on Samui Island, Surat Thani Province, Thailand. Pyrolysis was carried out in a 3-L bench-scale reactor at 450ºC using a 3% spent FCC catalyst. PE, PP, PS, and mixed plastic waste were used as feedstocks. The results showed that the pyrolysis of PS produced the most liquid product (91.44 wt%), whereas the pyrolysis of PE produced the highest percentage of diesel range product (36.60 wt%). Furthermore, the results of the analysis revealed that the characteristics of diesel from improved PE pyrolysis oil by naphtha removal were similar to those of commercial diesel B7. According to the cost-benefit analysis, the operating costs of pyrolysis oil and improved diesel were 0.37 and 0.65 USD/L, respectively, which were lower than the current market price of diesel B7. The findings of the study demonstrated the feasibility of converting plastic waste from MSW on Samui Island into alternative energy using eco-friendly and cost-effective technology.